Analisis Manajemen Waktu dan Biaya Rehabilitasi Paving Taman Bunga Kabupaten Sumenep - Ali Zainal Abidin (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Effective time and cost management is essential in construction projects to prevent delays and cost overruns. This study analyzes the time and cost management of the Rehabilitation Project of Flower Garden (Taman Bunga) Paving in Sumenep Regency, with a total contract value of IDR 810,128,000. A qualitative approach was employed using field observations, interviews, and document analysis as data collection methods. Data were analyzed by comparing planned versus actual project schedule and cost. Results showed that project implementation experienced two Contract Change Orders (CCO) redistributing work volumes without altering the total contract value. Significant schedule deviations occurred, reaching a cumulative gap of 41.49% at Week IV (planned 61.23% vs. actual 19.74%). Nevertheless, the project was completed at 100% by Week IX through overtime and additional labor. The Schedule Performance Index (SPI) fell as low as 0.32 in Week IV, indicating critical delay. The Cost Performance Index (CPI) remained at 1.0, confirming no cost overrun. Key delay factors included vegetation removal complexity, CCO administrative processes, adverse weather, and material procurement difficulties—particularly custom-order paving blocks. The study recommends enhanced pre-construction material surveys, comprehensive risk contingency planning, and systematic Critical Path Method (CPM) scheduling for similar future projects.